Illuminating Teachers' Voice and Perspectives on English Language Teaching in Secondary Schools in Northern City of Jordan - Alshirah, Salm Fankhour Alwan (2012)
The purpose of this qualitative case study was to shed light on teachers' perceptions and experiences on the challenges and problems that they encounter in teaching English as a foreign language in Jordan. The respondents of the study were purposefully selected to get an in-depth understanding on the process of teaching and learning English in Jordan. The primary respondents were five English teachers working in two secondary schools located at the north of Jordan. Besides teachers, six students, one school principal, two English supervisors, two English professors, two curriculum designers, three ministry officers, and two parents participated in the study to get a holistic picture on the case that was being investigated. Data collection was done using various methods primarily through interview, and complemented by class observation, photographs, and document analysis. The findings revealed that there are various problems with the teaching of English in Jordan. These include teachers’ competency and proficiency and general weaknesses on using the English language, ineffectiveness of teachers' training programs, teachers’ low motivation, and job satisfaction, poor working environment, poor interaction between teachers and students, teachers and parents, teachers and principals, and cooperation among teachers themselves, discipline problems, teachers' workloads, burnt-out syndromes among teachers, and shortage of learning materials in the Jordanian schools. The research ends by extending various recommendations particularly to the important stakeholders in Jordan to optimize the process of teaching English in the future.